Combined molecular and clinicopathologic characterization of feline coronavirus infection in cats from a multicat shelter - Fia Amalia; Madarina Wasissa; Siti Isrina Oktavia Salasia; Fajar Budi Lestari (Jurnal Medik Veteriner, 2026)
Molecular detection of feline coronavirus (FCoV) is essential for diagnosing feline infectious peritonitis (FIP). This study aimed to confirm FCoV infection in clinically suspected cats and to describe the associated hematological and cytological changes. Reverse transcriptase polymerase chain reaction (RT-PCR), targeting the N gene, was performed on 20 cats exhibiting clinical signs consistent with FCoV infection, including vomiting, diarrhea, abdominal effusion, rhinitis, uveitis, and ataxia, yielding the expected 386 bp amplicon in all cases. Ascitic fluid was preferred for RT-PCR when available, whereas blood samples were analyzed for hematology. Hematologic profiles revealed consistent inflammatory changes. The mean total leukocyte count was 22.8 ± 12.1 × 10³/µL, and the mean platelet count was 769 ± 505 × 10³/µL. Neutrophilia and leukocytosis were the most common abnormalities, observed in 55% (11/20) of cats, followed by monocytosis in 15% (3/20), lymphopenia in 5% (1/20), and lymphocytosis in 30% (6/20). Platelet counts showed marked variation, ranging from severe thrombocytopenia in 40% (8/20) to extreme thrombocytosis in 35% (7/20). Cytologic examination of ascitic fluid from five cats revealed macrophage-predominant exudates with moderate numbers of neutrophils and few lymphocytes. Macrophages were often vacuolated and contained phagocytosed debris, whereas some neutrophils appeared degenerated. The background consisted of proteinaceous material consistent with a high-protein effusion. The integration of molecular, hematologic, and cytologic findings provides a multimodal diagnostic approach that improves diagnostic reliability. These findings emphasize the importance of combining PCR with clinicopathological data to enhance the early and accurate detection of FIP in multicat environments.